PENGARUH PEMBELAJARAN BERBASIS KECERDASAN INTERPERSONAL TERHADAP HASIL BELAJAR STATISTIKA DASAR MAHASISWA (DITINJAU DARI PERBEDAAN GENDER) - Nurfadilah Mahmud; Rezki Amaliyah AR; Nursafitri Amin; Muhammad Jufri; Alimuddin; Zaiful Nur (Universitas Sulawesi Barat, 2019)
Interpersonal intelligence-based learning system is very important for prospective teacher because teaching, as profession, needs a good and effective social competence to communicate with students. Everyone has different degree of interpersonal intelligence, and also different in regard of mathematics learning achievement especially when gender is considered. This research was a pre-experimental research which aimed to know the influence of interpersonal intelligence-based learning system to sudents’ learning achievement in Basic Statistics class of mathematics education students/ prospective teachers in FKIP UNSULBAR by considering gender differences. Purposive random sampling was used as the sampling method and 16 male students and female students respectively were selected as the research subjects. Learning achievement was collected from Basic Statistic learning achievement test and was analyzed descriptively and inferensially. The results of the research show that the average of male srudents’ learning achievement in Basic Statistics (74,25) is higher than female students’ (66,00). While hypothesis testing shows significancy value of o.oo5, which is lower than α=0.05. It means there is a difference in regard of the average of Basic Statistics learning achievement between male and female students who participate in interpersonal intelligense-based learning system.